Long-Lasting In Vivo Effects of the Cannabinoid CB1 Antagonist AM6538 - Paronis, Carol A; Chopda, Girish R; Vemuri, Kiran; Zakarian, Ani S; Makriyannis, Alexandros; Bergman, Jack (The Journal of pharmacology and experimental therapeutics, 2018)
AM6538 is a cannabinoid antagonist that binds CB1 receptors expressed in HEK-293 cells in a wash-resistant manner. The effects of AM6538 in live animals has not previously been established. We characterized the antagonist effects of AM6538 in male mice, using a warm-water tail-withdrawal assay, and in male squirrel monkeys trained to discriminate the CB1 agonist AM4054 from vehicle. The cannabinoid agonists WIN 55,212, Δ -tetrahydrocannabinol (THC), and AM4054 all produced 100% maximum possible antinociceptive effects in mice following vehicle pretreatment. One-hour pretreatment with increasing doses of AM6538 (0.1-10 mg/kg) produced first rightward, then downward shifts of the agonist dose-effect functions. Rimonabant, 1-10 mg/kg, produced parallel rightward shifts of the AM4054 dose-effect functions, and baseline effects of AM4054 were nearly recovered within 24 hours following 10 mg/kg of rimonabant. In contrast, in mice treated with 10 mg/kg of AM6538, antagonism of THC or AM4054 lasted up to 7 days. AM6538 also antagonized the discriminative stimulus effects of AM4054 in squirrel monkeys in a dose-related manner, and the effects of 3.2 mg/kg of AM6538 endured for more than 7 days. The effective reduction in CB1 receptor reserve was used to calculate the relative efficacy (tau values) of WIN 55,212, THC, and AM4054 in mice and of AM4054 monkeys, with results indicating that THC has a lower efficacy than WIN 55,212 or AM4054 in mice. These results demonstrate that AM6538 is a long-acting CB antagonist in vivo, and further suggest that differences in CB efficacy can be revealed in behavioral assays following AM6538 treatment.